Removal of copper, mercury and arsenic ions at various pH levels using iron modified montmorillonite incorporated in polycaprolactone - De Jesus, Lance C.; Dusaban, Gelli Anne N.; Cruz, John Kenneth A. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Industrialization has led to the increase of heavy metal contamination in the environment that poses a great threat to human health. Copper, mercury and arsenic are widely recognized as toxic heavy metals that is increasingly polluting different bodies of water. In this study, iron modified montmorillonite incorporated in polycaprolactone (Fe-MMT PCL) via electrospinning was fabricated for the removal of Cu, Hg and As ions through the process of adsorption. Percent metal removal and adsorption capacity were investigated as a function of pH. The optimum values for percent metal removal of Cu, Hg and As ions are 97.33%, 84.75% and 26.48%, respectively. Highest adsorption capacity measured for each ion is as follows: 6.07 mg g -1 for Cu, 4.69 mg g -1 for Hg and 0.04 mg g -1 for As. It was concluded that varying pH and ion type significantly affects the percent metal removal of Fe-MMT PCL.
Thesis (B.S. Materials Engineering)--University of the Philippines Diliman
Keywords: Sewage -- Purification -- Heavy metals removal; Montmorillonite